Penegakan Hukum Terhadap Pelanggaran Protokol Kesehatan yang Dilakukan Masyarakat Pada Masa Pandemi Covid-19 di Kota Ambon - Sherly Adam; Reimon Supusepa; Jacob Hattu; Iqbal Taufik (Faculty of Law, Universitas Pattimura, 2021)
This study aims: 1. To determine and analyze law enforcement against violations of health protocols during the Covid-19 pandemic in Ambon City. 2. To find out and analyze the application of sanctions for violations of health protocols committed by the community during the Covid-19 pandemic in Ambon City. This research was conducted using a normative juridical research using a statutory approach, a conceptual analysis approach which is a descriptive study of qualitative analysis. The results of this study indicate that Law Enforcement against violations of health protocols during the Covid 19 pandemic in Ambon City is carried out based on statutory regulations, by limiting Community Activities (PKM), Large-Scale Social Restrictions (PSBB) as a form of law enforcement against health protocol violations. during the Covid 19 pandemic in Ambon City through socialization in preventing the spread of the Covid 19 virus and Large-Scale Social Restrictions (PSBB) by applying sanctions against offenders. However, law enforcement against violations of health protocols has not been carried out properly. This is due to the fact that health protocol violations are still occurring in Ambon city. 2. Imposing sanctions for violations of health protocols during the COVID-19 pandemic in Ambon city which is regulated in the Ambon City Mayor's Regulation on PSBB by applying written warning sanctions, administrative sanctions, social sanctions and criminal sanctions to violators. However, the application of sanctions against violators has not provided a deterrent effect on health protocol violators.